Ulama, Kitab Kuning and Al Washliyah Madrasah in Contemporary Indonesia - Ja'far, Ja'far; Asrul, Asrul (Hikmah, 2023)
This article examines the works of Al Washliyah ulama in Arabic and Malay written in Arabic script. Their works are commonly referred to as Kitab Jawi. This study adopts a literature research with a historical approach, using Mestika Zed's library research model. It utilizes Al Washliyah ulama’s works as the primary reference. The primary data was then analyzed using the content analysis method. The study corroborates the findings of Martin van Bruinessen, Zamakhsyari Dhofier, and Azyumardi Azra, indicating that Al Washliyah ulama has taught yellow book texts at various levels in Al Washliyah madrasas. On the other hand, they have written books in Arabic and Malay with Arabic script. Some of their works have not been republished and are no longer referenced by current Al Washliyah students. Conversely, some of their other works remain republished and references for Al Washliyah students. Their books may be classified further into elementary, intermediate, and advanced books. The results of this study have implications for the enrichment of Islamic literature, especially those sourced from the work of Al-Washliyah scholars